Perencanaan Ulang Jembatan Semut dari Tipe Gelagar Beton Menjadi Jembatan Rangka Baja Bentang Tunggal - Moch. Edra Aurick Aryanta (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The development of transportation infrastructure in Indonesia continues to be prioritized to enhance regional connectivity, including the maintenance and replacement of bridges that have exceeded their service life. The Semut Bridge in Surabaya, originally a three-span reinforced concrete girder bridge, has experienced structural deterioration due to corrosion and the presence of a central pier obstructing river flow. These conditions have reduced hydraulic capacity, increased sedimentation risk, and heightened the potential for flooding. This study redesigns the Semut Bridge by converting the existing structure into a single-span Howe truss steel bridge. The load analysis refers to SNI 1725 using the Load and Resistance Factor Design (LRFD) method, while structural modeling was carried out both manually and with SAP2000 software. The planning includes the vehicle deck slab, composite girders, main truss members, connections, elastomeric bearings, and abutments. The results show that the bridge deck uses a 20 cm thick reinforced concrete slab with a one-way reinforcement system. Composite girders employ WF profiles, connections use shear connector studs with 25 mm diameter, and the main truss members adopt WF 900×300×16×38 profiles. The total concrete volume required is 282.6 m³, and the estimated steel demand reaches 122,383.79 kg. The single-span design eliminates the central pier, thereby improving river flow capacity while providing a structurally efficient, durable, and easily maintained solution.